ANALISA KRITIS: HAK KONSTITUSIONAL PROFESI GURU - Triwahyu Budi Utomo (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Problems constitutional rights of citizens, especially the constitutional right of Master in performing the tasks their profession very interesting to be studied in depth. Many phenomena memprihatin happens to teachers in performing the duties of his profession. Legal framework is indispensable for teachers in carrying out the duties of his profession. Konstkitusi rights are the legal rights of the highest level, how 1945 has dimanademen able to give a guarantee of protection for teachers in carrying out the duties of his profession. Constitutional rights contained in the 1945 Constitution before the amendment is 7 chapters that consist of Article 27 paragraph (2), article 28, article 29 (paragraph (2), Article 30 paragraph (1), Article 31 paragraph (1) and Article 32. Meanwhile, after the Second Amendment in 2000, the overall material provisions of the rights of human rights in the 1945 Constitution, which when combined with the various provisions contained in the legislation relating to human rights, can be grouped into four groups containing 37 grains provisions , The teacher is a profession that vulnerable groups receive treatment that could interfere with the task of his profession, thus requiring special treatment for access protection and fulfillment of the constitutional right to avoid the violence and achieve justice with dignity. Constitutional rights for teachers in carrying out professional duties is guaranteed in the Law on Teachers and Lecturers and implied the existence of protection for teachers in implementing professional duties which include: (1) protection of the law; (2) the protection of the profession: and (3) the protection of health and safety.